2021
DOI: 10.48550/arxiv.2107.04939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toward Certifiable Motion Planning for Medical Steerable Needles

Mengyu Fu,
Oren Salzman,
Ron Alterovitz

Abstract: Medical steerable needles can move along 3D curvilinear trajectories to avoid anatomical obstacles and reach clinically significant targets inside the human body. Automating steerable needle procedures can enable physicians and patients to harness the full potential of steerable needles by maximally leveraging their steerability to safely and accurately reach targets for medical procedures such as biopsies and localized therapy delivery for cancer. For the automation of medical procedures to be clinically acce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Most of the RCS* in Figure 9 a,b are below the RCS or RCS* curves, due to the different sample sizes of each algorithm and the 1 s per planning time frame, which we abandoned to estimate the total cost by integrating the curves with the x-axis. Critically, Meng Yu Fu’s experiments [ 15 ] have shown that RCS* exhibits significant performance in terms of actual total consumption cost. The average and cost before reaching the lowest of the six groups in Table 2 and Table 3 have been integrated into Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the RCS* in Figure 9 a,b are below the RCS or RCS* curves, due to the different sample sizes of each algorithm and the 1 s per planning time frame, which we abandoned to estimate the total cost by integrating the curves with the x-axis. Critically, Meng Yu Fu’s experiments [ 15 ] have shown that RCS* exhibits significant performance in terms of actual total consumption cost. The average and cost before reaching the lowest of the six groups in Table 2 and Table 3 have been integrated into Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Meng Yu Fu et al [ 15 ] presented the first resolution-complete but not the resolution-optimal manipulable needle motion planner (RCS), for steerable needles. If there is a puncture path, the RCS will find motion planning in a limited time, provided the parameter resolution is good enough, but it does not guarantee motion planning costs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides more recent attempts exploiting evolutionary strategies [ 165 ] or machine learning techniques [ 166 ], the majority of the state-of-the-art planners are graph-based methods, such as A* [ 167 , 168 ], or sampling-based methods, such as Rapidly exploring Random Trees (RRT) [ 169 , 170 , 171 , 172 ] and Adaptive Fractal Trees (AFT) [ 173 , 174 ]. In [ 175 ], the authors presented a new searched-based planner based on [ 176 , 177 ] for steerable needles that guarantees completeness under some clinically reasonable assumptions. This is important because having the formal proof that if a plan exists, it will be found and if it does not exist, the user will be notified may prove to be an important aspect for medical certification.…”
Section: Robotics Solutionsmentioning
confidence: 99%